COMPUTER-AIDED SYSTEM FOR DETERMINING INDUSTRIAL MACHINERY OPTIMAL REPLACEMENT PERIOD (Journal of Information and Communication Technology, 2013)
This paper focuses on bridging the gap between age-dependent optimal replacement theory and its industrial applications by identifying and incorporating the criteria considered by field (maintenance) engineers before embarking on industrial machine replacement, into an existing model to make it appropriate industrial-wise. We aim to economically quantify the identified criteria and thereafter integrate them into the weighted average cost of running the machine from the time of its installation to the date of analysis to alleviate the drudgery in using this approach most especially when multiple machines are to be analyzed, the Machine Replacement Analysis Software (MRAS) was developed and its implementation was done using data obtained from a Grinder used for cocoa processing. A curve with polynomial function and coefficient of determination of 0.935 was obtained and this implies replacing the machine after the seventh year of usage.